Femoral access‐related complications during percutaneous transcatheter aortic valve implantation comparing single versus double Prostar XL device closure. Issue 7 (2nd September 2015) - Saleh, Nawsad; De Palma, Rodney; Settergren, Magnus; Rück, Andreas
Abstract : Objectives: To evaluate the efficacy and safety of a double Prostar XL suture‐based closure technique compared to a conventional single Prostar XL technique in elective transcatheter aortic valve implantation (TAVI) via the common femoral artery. Background: TAVI is recommended as a treatment for symptomatic severe aortic stenosis for those who are at high or prohibitive risk of surgical valve replacement. Vascular complications remain the most frequent category of procedural complication. The most efficacious and safest percutaneous suture‐based closure technique is unknown. Methods: Prospective observational study of Prostar XL device closures used in 126 consecutive patients between 2012 and 2014. Single Prostar XL closure was used in 63 patients and double Prostar XL closure in a further 63 patients. Outcomes from the groups were compared. All patients were treated transfemorally through an 18Fr sheath. Technical success was defined as hemostasis not requiring interventional or surgical repair during hospital admission. Bleeding and vascular complications were defined using the second consensus of the valvular academic research consortium (VARC‐2) criteria. Results: The cohort was aged 83+/‐6 and 48% were female with a logistic Euroscore of 24+/‐11.6. Technical success was 86% and 98% respectively ( P = 0.017) with systematic single and double Prostar XL closure. Composite VARC‐2 vascular and bleeding complications occurred more frequently in the single Prostar XL group compared to the double Prostar XL group (10 [16%] v 3 [5%] P < 0.04, and 17 [27%] v 6 [10%] P < 0.004). Conclusion: A systematic double Prostar XL closure technique for large caliber arterial access sites during TAVI is feasible, safe and associated with fewer technical failures, fewer vascular complications, and less bleeding compared with single Prostar XL. © 2015 Wiley Periodicals, Inc.